Implementation of Organizational Agility Strategies to Meet The Challenges of Digital Transformation in Government Organizations - Agung Fachridian; Abdul Haeba Ramli; Lizio Marcel de Araujo (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2024)
Digital transformation has become essential for all organizations as innovation and digital technology continue to evolve. This research focuses on the impact of organizational agility on digital transformation in the government sector, as well as the role of Collaborative Knowledge Creation (CKC), innovation, and Digital Transformational Leadership (DTL) as antecedents and factors that influence organizational agility. Quantitative research using the Structural Equation Model (SEM) method began in 2023. The unit of analysis involved 103 work units in government organizations that focus on the development of science and technology (S&T). The results of this study show that the role of organizational agility can improve digital transformation in the government sector, and the role of innovation and DTL as antecedents and factors, can affect organizational agility. This shows that in driving change towards digital transformation in organizations, the role of organizational agility is very important. This research has managerial implications for government organizations, especially organizational leaders and work unit leaders in building digital transformation. Organizational leaders must realize that implementing sound management strategies fostering organizational agility, including designing adaptive policies, cultivating a responsive organizational culture, and establishing structures that promote collaboration and innovation can facilitate government organizations digital transformation.